Persistence of overconfidence in young children: Factors that lead to more accurate predictions of memory performance. Issue 2 (4th March 2018) - Was, Christopher A.; Al-Harthy, Ibrahim S.
Abstract: Young children are typically overconfident regarding both cognitive abilities. This overconfidence may be due to development underpinnings. Previous research has demonstrated that children exhibit robust and persistent overconfidence in a simple memory-recall task. Two experiments investigated this overconfidence in 1st–4th and 4th–6th grade students. In the first experiment, we explored both the development of accurate predictions of recall and young students' confidence in their memory performance predictions. It was found that not until 4th grade did students' overconfidence begin to wane. In the second experiment, we investigated a condition under which 4th–6th graders might make more accurate predictions of their ability to recall simple stimuli, specifically, when the items to be remembered were unfamiliar to the students. The results confirmed our overconfidence in familiarity hypothesis. We discuss these findings in the context of metacognition.